Vibro-acoustic analysis of a rail transit continuous rigid frame box girder bridge based on a hybrid WFE-2D BE method. (1st January 2020) - Song, Lizhong; Li, Xiaozhen; Zheng, Jing; Guo, Min; Wang, Xinxin
Highlights: A hybrid WFE-2D BE method for rapid prediction of bridge-borne noise is proposed. A vibration and noise test conducted on a rigid-frame box-girder is introduced. The vibro-acoustic characteristics of the rigid-frame box-girder are analysed. Abstract: In this paper, a hybrid waveguide finite element (WFE) and two-dimensional boundary element (2D BE) method for the rapid calculation of bridge-borne noise is first proposed and then validated by the results of a vibration and noise field test conducted on a 3 × 40 m concrete continuous rigid-frame box-girder bridge in the Guangzhou Metro System. The advantages of the proposed method are discussed by comparison with a hybrid FE-3D BE model. Finally, the vibro-acoustic characteristics of the bridge are analysed. The results show that the dominant frequency range of the local vibration and radiated noise of the bridge is 63–200 Hz. The WFE model of the bridge has a higher efficiency and nearly the same accuracy compared with the traditional FE model. The 2D BE model of the bridge has a significant higher efficiency compared with the 3D BE model but loses a certain degree of accuracy. The sound fields of the region above the bridge, the region just below the bridge and the lower region beside the bridge are mainly affected by the sound radiated from top and flange slabs, flange and bottom slabs, web slab, respectively. It is beneficial for noise reduction to increase the bridge deck thickness or the bottom slab width.